Application of the Goal Programming Method in Nurse Scheduling at RSUD Dr. Hadrianus Sinaga Pangururan - Larry Ronaldo Samosir; Faiz Ahyaningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to establish an effective and optimal nurse schedule at the Regional General Hospital dr. Hadrianus sinaga Pangururan. RSUD dr.Hadrianus Sinaga Pangururan is still scheduling nurses manually with a total of 20 nurses and has three work shifts namely morning, afternoon and evening. As a result of manual scheduling, it takes quite a long time and is less efficient due to imbalances in the distribution of shifts. The method used to solve nurse scheduling problems is Goal Programming. Goal Programming is the development of linear programs that are used to solve linear programming problems with multiple objective functions. In modeling this scheduling problem, there are two systems of constraints that must be met, namely the main constraints and additional constraints. The main obstacle is hospital rules that must be complied with while additional obstacles are hospital rules that are still given tolerance for violations. In modeling the nurse scheduling problem, each problem is converted into a mathematical model and the completion of the goal programming model is assisted by LINGO software. From the LINGO output, the results show that nurse scheduling using goal programming meets all system constraints, while the hospital's manual schedule does not meet system constraints.